2014
DOI: 10.1111/jrh.12058
|View full text |Cite
|
Sign up to set email alerts
|

Rural‐Urban Disparities in School Nursing: Implications for Continuing Education and Rural School Health

Abstract: Our findings support the provision of online courses and telehealth content to address urban-rural disparities in school nursing education and support rural school health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 58 publications
1
29
0
Order By: Relevance
“…However, rural nurses were significantly less likely to have had access to post-nursing school asthma training, a finding consistent with previous research on disparities in rural-urban school nursing continuing education (Ramos, Fullerton, Sapien, Greenberg, & Bauer-Creegan, 2014). Tailored asthma training using telehealth or online course technologies could address access barriers experienced by rurally-located school nurses, such as distance or time constraints.…”
Section: Discussionsupporting
confidence: 87%
“…However, rural nurses were significantly less likely to have had access to post-nursing school asthma training, a finding consistent with previous research on disparities in rural-urban school nursing continuing education (Ramos, Fullerton, Sapien, Greenberg, & Bauer-Creegan, 2014). Tailored asthma training using telehealth or online course technologies could address access barriers experienced by rurally-located school nurses, such as distance or time constraints.…”
Section: Discussionsupporting
confidence: 87%
“…School nurses were only moderately comfortable counseling students and lacked confidence when delegating administration to other staff members, reflected in the high demand for training on the use of opioids and naloxone. The strong preference for online training modules may be due to the ability to overcome barriers including cost, time constraints, work and family commitments, 26 and could minimize urban–rural training disparities. 26 Additionally, local workshops may provide an effective method of training.…”
Section: Discussionmentioning
confidence: 99%
“…The strong preference for online training modules may be due to the ability to overcome barriers including cost, time constraints, work and family commitments, 26 and could minimize urban–rural training disparities. 26 Additionally, local workshops may provide an effective method of training.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study noted disparities between rural and urban school nurses, with rural nurses being less likely to receive continuing education on an array of topics, including diabetes [26]. As guidelines are updated, rural public health nurses must also update their knowledge to stay clinically competent.…”
Section: Continuing Education For Rural Health Nursesmentioning
confidence: 96%
“…Research has concluded that rural nurses often receive less continuing education which is a barrier in staying up to date [26]. Given the importance of prompt prediabetes identification, this study sought to assess rural public health nurses' prediabetes knowledge base, and evaluate the usefulness of a onetime education intervention.…”
Section: Continuing Education For Rural Health Nursesmentioning
confidence: 98%